Resembling the bottleneck effect in p53 core network including the dephosphorylation of ATM by Wip1: A computational study - Wang, DaoGuang; Wang, Yaolai; Lü, Huaping; Wu, Zhangqi; Liang, Xiaoming (Frontiers in Physics, 2022)
As one of the key proteins, wild-type p53 can inhibit the tumor development and regulate the cell fate. Thus, the study on p53 and its related kinetics has important physiological significance. Previous experiments have shown that wild-type p53-transcribed phosphatase one protein Wip1 can maintain the continuous oscillation of the p53 network through post-translational modification. However, the relevant details are still unclear. Based on our previous p53 network model, this paper focuses on the modification of Wip1 dephosphorylated ataxia telangiectasia mutant protein ATM. Firstly, the characteristics and mechanism of p53 network oscillation under different numbers of DNA double strand damage were clarified. Then, the influence of ATM dephosphorylation by Wip1 on network dynamics and its causes are investigated, including the regulation of network dynamics transition by the mutual antagonism between ATM dephosphorylation and autophosphorylation, as well as the precise regulation of oscillation by ATM-p53-Wip1 negative feedback loop. Finally, the cooperative process between the dephosphorylation of ATM and the degradation of Mdm2 in the nucleus was investigated. The above results show that Wip1 interacts with other components in p53 protein network to form a multiple coupled positive and negative feedback loop. And this complex structure provides great feasibility in maintaining stable oscillation. What’s more, for the state of oscillation, the bottleneck like effect will arise, especially under a certain coupled model with two or more competitive negative feedback loops. The above results may provide some theoretical basis for tumor inhibition by artificially regulating the dynamics of p53.